Initial treatment efficacy and safety of durvalumab plus tremelimumab combination therapy in unresectable hepatocellular carcinoma in clinical practice - Tetsu Tomonari; Joji Tani; Yasushi Sato; Hironori Tanaka; Akihiro Morishita; Koichi Okamoto; Yutaka Kawano; Masahiro Sogabe; Hiroshi Miyamoto; Tetsuji Takayama (JGH Open)
Abstract Background and Aims We aimed to evaluate the efficacy and safety of durvalumab plus tremelimumab (Dur + Tre) combination therapy in patients with unresectable hepatocellular carcinoma (uHCC) in clinical practice. Methods We retrospectively evaluated 37 patients with uHCC from our institutions between April 2023 and January 2024. Patients were divided into first‐ and later‐line groups for analysis of antitumor efficacy, adverse events (AEs), and transition rate to second‐line treatment according to the Response Evaluation Criteria in Solid Tumors (RECIST). Results The disease control rate (DCR) for the first‐line group was 80.9%, which was significantly higher than that for the later‐line group (50%). The incidence of immune‐related AEs (irAEs) was 24.3%, with grade 3 or higher irAEs including increased transaminase (8.1%), diarrhea (8.1%), and adrenal insufficiency (2.7%). The rates of drug withdrawal and discontinuation owing to AEs were 23.8% and 19%, respectively, in the first‐line treatment and 31.2% and 12.5%, respectively, in the later‐line treatment, with no significant difference. Analysis of changes in liver reserve using the albumin–bilirubin (ALBI) score showed no obvious loss of liver reserve for up to 12 weeks. The transition rate from first‐ to second‐line therapy after progressive disease (PD) was as high as 94.7%. Conclusion The efficacy and safety of Dur + Tre in clinical practice were comparable to those reported in a recent phase III trial. The first‐line Dur + Tre therapy had a higher DCR than that of the later lines, and the transition rate to second‐line therapy was considerably high, suggesting that Dur + Tre therapy would be more beneficial in first‐line treatment.